Stereotype and Creation - MATEVOSYAN, LIANNA (Bulletin of Yerevan University H: Russian Philology, 2021)
Relying on the standard as the nucleus of linguistic system in a number of stereotypical situations, an individual often not only alters, but also destroys the latter, often creating something new. The stimulus appears to be a desire to be unique, not to disappear, not to dissolve in stereotype, not to lose one’s own self. In this case a trend towards dynamism and expression steps forward.